Penerapan Prosedur Pelayanan Breakfast A La Carte selama Masa Pandemi Covid-19 - Mudara, I Made Bayu; Rinayanthi , Ni Made (Institut Pariwisata dan Bisnis Internasional, 2024)
Penerapan prosedur adalah pelayanan yang dilakukan ketika ingin menyajikan makanan kepada tamu. Penerapan prosedur pelayanan breakfast a la carte di Rama Beach Resort and Villas dimana pramusaji menyambut tamu yang datang ke restoran, menyanyakan nomor kamar tamu, nama tamu, dan jumlah tamu yang akan sarapan. Penelitian ini mengenai penerapan prosedur pelayanan breakfast a la carte di Rama Beach Resort and Villas selama masa pandemi covid-19. Tujuan penelitian ini untuk mengetahui apa saja kendala yang dihadapi saat pelayanan a la carte dan bagaimana seharusnya penerapan SOP yang baik di Dewi Shinta Restaurant Rama Beach Resort and Villas. Penelitian ini menggunakan data primer dan sekunder melalui observasi dan wawancara. Data dikumpulkan dengan melakukan observasi tentang SOP yang diterapkan di Rama Beach Resort and Villas. Berdasarkan hasil observasi yang dilakukan terdapat 2 prosedur pelayanan A La Carte breakfast yang tidak sesuai dengan Standard Operational Procedure. Prosedur yang belum diterapkan adalah unfolding the guest napkin, please the guest choose the food at the menu. The apllication procedures are services that are carried out when you want to serve food to guests. Implementation of a la carte breakfast service procedures at Rama Beach Resort and Villas where the waiter welcomes guests who come to the restaurant, asks for the guest room number, guest name, and number of guests who will have breakfast. This research concerns the implementation of a la carte breakfast service procedures at Rama Beach Resort and Villas during the Covid-19 pandemic. The purpose of this research is to find out what are the obstacles faced when serving a la carte and how good SOPs should be implemented at Dewi Shinta Restaurant Rama Beach Resort and Villas. This study uses primary and secondary data through observation and interviews. Data was collected by observing SOPs applied at Rama Beach Resort and Villas. Based on the results of observations made, there were 2 procedures for A La Carte breakfast services that were not in accordance with the Standard Operational Procedure. And the procedure that has not been implemented is unfolding the guest napkin, please the guest choose the food in the menu.